Tata Laksana E-Procurement Di Kabupaten Pangkajene Dan Kepulauan - Nur Ikhsan; Andi Nuraeni Aksa; Adnan Ma'ruf (Department of Public Administration, Muhammadiyah University of Makassar, 2018)
The main purpose in this research is implementation understanding of E procurement also understand of supporting and E procurement obstacle factor in the pangkep district. E-procurement is an innovation in the use of Information Technology for the benefit of public services. Based on this, researchers are encouraged to try to explain the implementation of E-procurement in the Pangkep district. Amount of informan in this research are five people. type of research is qualitative with kind of fenomenology research which is focused on human living experiences. Collecting data technique are using observation method, interview and documentation. Data analysis using interactive analysis models. Research result refers to unoptimalitation of E procurement implementation in the Pangkep district. This implementation seen by the stage of the E procurement aspect altough appropriated absolutely unaccomplished. In accordance with the implementation exist in president regulation in article 107 year 2010 number 54. This can be seen indicator (1) E-tendering (2) E-bidding (3) E-catalogue and(4) E-purchasing. Supporting factor in this implementation is strategy of loyalty provider whereas obstacles are divergents and postponement. Key word: E-service, Job Fair, Pangkep Regency.ABSTRAKTujuan penelitian adalah untuk mengetahui Tata Laksana E-procurement dan mengetahui faktor pendukung dan penghambat E-procurement di Kabupaten Pangkajene dan Kepulauan. E-procurement merupakan suatu inovasi dalam pemanfaatan Teknologi Informasi untuk kepentingan pelayanan publik. Berdasarkan hal tersebut peneliti terdorong untuk mencoba menjelaskan Pelaksanaan E-procurement di Kabupaten Pangkajene dan Kepulauan. Jumlah informan dalam penelitian ini adalah 05 orang. Jenis penelitian yang digunakan adalah kualitatif dengan tipe penelitian fenomenologi yaitu menekankan pada subyektivitas pengalaman hidup manusia. Teknik pengumpulan data menggunakan metode observasi, wawancara dan dokumentasi. Analisis data dengan menggunakan model analisa interaktif. Hasil penelitian menunjukkan bahwa Pelaksanaan E-procurement di Kabupaten Pangkajene dan Kepulauan belum sepenuhnya terlaksana dengan optimal hal ini dilihat dari aspek tahapan E-procurement dimana penyedia yang meskipun telah sesuai dengan prosedur namun belum sepenuhnya berhasil dalam melaksanakan tahapan E-procurement sesuai dengan tujuan yang terdapat dalam Peraturan Presiden No. 54 tahun 2010 pasal 107. hal ini dilihat dari indikator (1) E-tendering (2) E-bidding (3) E-catalogue dan (4) E-purchasing. Faktor Pendukung dalam pelaksanaan ini adalah Strategi dan Loyalitas penyedia sedangkan faktor yang menjadi penghambat adalah penyimpangan dan penundaan.Kata Kunci: Tata Laksana, E-Procurement, Kabupaten Pangkep.